Aplikasi Kumer-Math Berbasis Pembelajaran Diferensiasi Terhadap Kemampuan Berpikir Kreatif Pada Materi Perbandingan Trigonometri - Rinda Sari; Hartono; Muhammad Firdaus (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2024)
This research aims to produce learning media in the form of Android applications that achieve valid, practical and effective criteria so that they are suitable for use. This research uses Research and Development (R&D) methodology. The steps for developing this application use the ADDIE model which stands for analysis, design, development, implementation and evaluation. The subjects in this research were class X SMA Negeri 1 Mempawah Hilir students. The instruments used in this research were media and material expert validation sheets, student and teacher response questionnaires, and posttests. The research results related to validity reached a validity level in the "Very Valid" category with media validity reaching 88.78% and material validity reaching 95.57%, reaching a level of practicality with the "Very Practical" criteria as indicated by the student response questionnaire which reached a score of 90, 13% and the response questionnaire given by the teacher reached a score of 93.08%, reaching a level of effectiveness with the criteria "Very Effective" based on the completion score determined by the school with test results showing the percentage of student completion getting a score of 91.67%. With this it can be concluded that the Kumer - Math application based on differentiation learning for creative thinking skills in trigonometry comparison material is very suitable for use.